Prevention and treatment for COVID-19 associated severe pneumonia in the Gambia (PaTS-COVID-19), a single-blinded randomized clinical trial: study protocol - Usuf, Effua; Brotherton, Helen; Nadjm, Behzad; Mohammed, Nuredin; Gai, Abdou; Sillah, Fatoumata; Johnson, Mary Grey; Jones, Chiquita Joquina; Sarr, Catherine; Babatunde, Hakeem Edun; Mohammad, Abul Khalie; Dibba, Bakary; et al. (International Journal of Clinical Trials, 2023)
Background: The coronavirus disease (COVID-19) pandemic resulted in an unprecedent global response for the development of COVID-19 vaccines. However, as viral mutations continue to occur, potentially decreasing the efficacy of currently available vaccines, and inequity of vaccine access continues, identifying safe and effective drugs to minimise severity of COVID-19 disease remains a priority. Methods: We designed an adaptive individually randomized single blinded non identical placebo-controlled trial to evaluate the safety and efficacy of repurposing licenced treatments for COVID-19 patients in an African setting. The trial has two cohorts: Cohort 1 recruits mild and moderate COVID-19 cases and their household contacts. Cases are actively followed up for 14 days, with a final visit at day 28. There are two co-primary endpoints: clinical progression to severe-pneumonia and persistence of the virus at day 14. The primary endpoint for household contacts is infection during a 14-day follow-up period. Cohort 2 recruits hospitalized patients with severe COVID-19 associated pneumonia followed up actively until discharge or death, and passively until day 90, with a final visit. The primary endpoint is clinical progression or death. Conclusions: This randomized trial will contribute African-specific data to the global response to COVID-19. Besides the efficacy of drugs on clinical progression, the trial will provide information on the dynamics of intra-household transmission. Trial registration: This study is registered with Clinical Trials.gov with registration number NCT04703608 and with Pan African clinical trials registry with registration number PACTR202101544570971.